Inhibition of the osteogenic differentiation of mesenchymal stem cells derived from the offspring of rats treated with caffeine during pregnancy and lactation. (3rd March 2016) - Reis, Amanda Maria Sena; Ocarino, Natália de Melo; Boeloni, Jankerle Neves; Gomes, Dawidson Assis; Goes, Alfredo Miranda; Ferreira, Andrea da Fonseca; Serakides, Rogéria
ABSTRACT: Caffeine is an alkaloid that is widely consumed due to its presence in drugs, coffee, tea, and chocolate. This compound passes to offspring through the placenta and milk; can cause teratogenic mutations; and reduces the formation, growth, and mass of bone. Because mesenchymal stem cells (MSCs) are responsible for generating the entire skeleton, we hypothesized that these cells are targets of caffeine. This study evaluated the osteogenic differentiation of MSCs derived from the offspring of rats treated with caffeine during pregnancy and lactation. Twenty-four adult Wistar rats were randomly divided into four groups, including one control group and three experimental groups treated with 25, 50, or 100 mg/kg of caffeine. At weaning, three 21-day-old pups from each dam in each group were euthanized for extraction of bone marrow cells for in vitro tests. Caffeine doses of 50 and 100 mg/kg significantly reduced the activity of alkaline phosphatase at 7, 14, and 21 days and the expression of collagen I at 21 days. However, the expression of gene transcripts for alkaline phosphatase, Runx-2, and bone sialoprotein, as well as the synthesis of mineralization nodules, decreased significantly in all groups treated with caffeine. The expression of osteocalcin was significantly reduced only in the group treated with 50 mg/kg caffeine. The caffeine that passes from the mother to the offspring during pregnancy and lactation reduces the osteogenic differentiation of MSCs. We propose that this reduction in the osteogenic potential of MSCs may be involved in the pathogenesis of osteopenia resulting from caffeine consumption.